Serosurvey of human T cell lymphotropic virus I/II among blood donors in Gombe (Nigeria) (2016)
Aim: This study was carried out to determine the prevalence of human T cell lymphotropic virus I/II (HTLV I/II) among blood donors at the Federal Teaching Hospital Gombe (FTHG), North-eastern, Nigeria. Methods: A total of 355 blood donors were recruited at the hematology department of FTHG for a hospital based crosssectional study and were screened/confirmed for HTLV I/II by ELISA and western blot methods. Results: Seroprevalence of HTLV I/II among the 355 participants with mean age of 30.77 years (±8.27) was 6.5% on screening with ELISA but confirmed to be 0% by western blot. Majority were males, 352 (99.2%) and mostly (45.9%) between 21–30 years of age. Donors for family replacements predominated (85.1%) with more than half (58.6%) being first time blood donors. Conclusion: This study reveals the absence of HTLV I/II among blood donors in Gombe Northeastern Nigeria. It also highlights the possibility of false positivity in some of the reported prevalence of HTLV I and II from some parts of Nigeria that were based on screening tests only. The importance of confirmatory testing in all research works on HTLV (including HTLV 3 and HTLV 4) is further strengthened with this study. There is however the need for a larger study and the use of molecular diagnostics to reconfirm this assertion.